2010
DOI: 10.1039/b9pp00113a
|View full text |Cite
|
Sign up to set email alerts
|

Fast decoloration of spironaphthooxazine bound to a poly(dimethylsiloxane) network

Abstract: Spironaphthooxazine (SNO) was attached to a three-dimensional network of polysiloxane through the allyloxy group on C-7 of the naphthalene ring of SNO, and the photochemical coloration and thermal decoloration behaviors of this material (Film-P) were examined by comparing their properties with those of model SNO having a 7-propyloxynaphthyl group in solution, in a doped polysiloxane film (Film-D), and in a doped PMMA film. For Film-P, the SNO units were connected to a part of the vinyl groups on the Si atoms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…When the large structural change is induced by the photochromic reaction, the thermal back reaction rate crucially depends on the viscosity of the polymer matrix [10,[19][20][21]. The ΔV ‡ is one of the effective measure to elucidate the structural change associated with chemical reactions because ΔV ‡ originates from the difference in the partial molar volumes between the initial state and the transition state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the large structural change is induced by the photochromic reaction, the thermal back reaction rate crucially depends on the viscosity of the polymer matrix [10,[19][20][21]. The ΔV ‡ is one of the effective measure to elucidate the structural change associated with chemical reactions because ΔV ‡ originates from the difference in the partial molar volumes between the initial state and the transition state.…”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated that the value of the activation free volume (ΔV ‡ ) for the thermal back reaction is an effective measure to evaluate the efficiency of the photochromic reaction in polymer matrix [17,18]. The other solution is to reduce the viscosity of a host polymer matrix [10,[19][20][21]. By using the soft polymer matrix such as siloxane or using the plasticizer, the glass transition temperature (Tg) of a polymer matrix is reduced effectively for the use of the host polymer matrix of photochromic molecules [10].…”
Section: Introductionmentioning
confidence: 99%
“…The second strategy is to facilitate the dye isomerization by providing softer (less steric hindrance) or void (free-volume) matrix environments. This has been accomplished by i) functionalizing the photochromic molecules with flexible tails, [46][47][48][49][50] ii) embedding the dyes in different media such as low glass transition and/or plasticized polymers, 51,52 hybrid organic/inorganic materials, [53][54][55] hydrogels, 56 or organogels, 57 and iii) encapsulating the molecules in the cages of hybrid mesostructured (nano)materials, [58][59][60][61][62] metal-organic frameworks, 63,64 and supramolecular assemblies. [65][66][67] The encapsulation was also explored by our group, which reported tunable photochromic properties (fast or reverse photochromism) in solid materials by embedding core-shell capsules into polymeric films, 20,68,69 a strategy that was also successfully extended to the fabrication of liquid-like thermochromic 70 and white-emitting 71 materials.…”
Section: Materials Horizons Accepted Manuscriptmentioning
confidence: 99%
“…50 It is well known that the thermal decoloration reaction rate decreases when SOs are placed in solid matrices such as polymer films. 51,52 Prolonged half-lives observed for SO2-SO5 are thought to be ascribed to their relatively large volume for isomerization. They may also be ascribed to their increased T g s since the decoloration experiments were performed at room temperature (300-306 K).…”
Section: General Properties Of So Derivativesmentioning
confidence: 99%